Complexity of the Einstein-Born-Infeld-massive black holes - B. Bahrami-Asl; S.H. Hendi (Nuclear Physics B, 2020)
Motivated by interesting correspondence between computational complexity in a CFT and the action evaluated on a WDW patch in the bulk, we study the complexity of the Einstein-massive black holes in the presence of BI nonlinear electrodynamics. The upper limit of Lloyd's bound according to the WDW patch is investigated and it is found that there are some physical intervals for massive parameters in which Lloyd's bound is held.